Denture Stomatitis with Systemic Disease in Elderly Patient. A Case Report - Rambe, Sarinah; Rifki, Ayudia; Ulfah, Khairiyah; Husna, Nurul; As Syifa, Salwa (Journal of Indonesian Dental Association, 2025)
ABSTRACT Introduction: Denture Stomatitis (DS) is a frequent condition that affects people who wear dentures, particularly the elderly. There are several contributing factors to denture stomatitis. Many local and systemic predisposing factors interact with one another. Case report: A 54-year-old female presented to Dental Hospital Universitas Syiah Kuala with a chief complaint of redness of the palate. Dentures currently seem loose and frequently fall out when speaking and chewing. Intraoral examination revealed diffuse erythematous, measuring >2 cm, red in color, number 2 (bilateral), irregular edges, located on the hard palate. Atrophic lesions, flat, measuring ±3x5cm, red in color, multiple, with diffuse borders and irregular edges, located dorsal of the tongue. Laboratory test results showed an increase in blood glucose levels, HbA1c and decrease in Hemoglobin, Hematocrit, Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH). Based anamnesis, clinical features and adjunctive examination was diagnosed Denture stomatitis with Diabetes Mellitus and slight Anemia. The treatment was Nystation oral suspension, Chlorhexidine Gluconate 0.2%, maintained oral health and improved nutrition. Conclusion: Denture stomatitis is a complex disorder that mostly affects the palatal mucosa of the upper jaw. Management of this condition must be comprehensive, starting with a proper diagnosis of the causative and risk factors, then directing treatment to the most significant factors specific to the patient.